Human Resource Management Practices and Organizational Commitment : A Comprehensive Review (2001-2016) - Ramaprasad, Badrinarayan S.; Nandan Prabhu, K. P.; Lakshminarayanan, Sethumadhavan; Pai, Yogesh P. (Prabandhan: Indian Journal of Management, 2017)
The primary purpose of this study was to synthesize empirical findings of studies that have investigated the relationship between HRM practices and organizational commitment (OC). We adopted a comprehensive review that covers empirical research on HRM - OC relationship, which was published between 2001 and 2016 in international peer-reviewed journals. A total of 63 empirical articles were included in this review. We adopted the content analysis method to synthesize the empirical findings on HRM - OC relationship and research methods adopted. Majority of the studies provided evidence of a positive association between HRM practices and OC. Evidence from this review pointed towards a significant mediating effect that the construct of OC exercised between HRM practices and different employee and organizational outcomes. Also, this review found support for an indirect relationship between HRM practices or systems and OC mediated by organizational environment characterized by factors such as, for example, work engagement, satisfaction with work, person - organization fit, and an enabling organizational climate.